Rietveld refinement of the low temperature crystal structures of Cs2XSi5O12 (X = Cu, Cd and Zn) - Bell, Anthony Martin Thomas (European Journal of Chemistry, 2021)
The synthetic leucite silicate framework mineral analogues Cs2XSi5O12 (X = Cu, Cd, Zn) were prepared by high-temperature solid-state synthesis. The results of Rietveld refinement, using 18 keV synchrotron X-ray powder diffraction data collected at low temperatures (8K X = Cu, Zn; 10K X = Cd) show that the title compounds crystallize in the space group Pbca and are isostructural with the ambient temperature structures of these analogues. The structures consist of tetrahedrally coordinated SiO4 and XO4 sharing corners to form a partially substituted silicate framework. Extraframework Cs cations sit in channels in the framework. All atoms occupy the 8c general position for this space group. In these refined structures, silicon and X atoms are ordered onto separate tetrahedrally coordinated sites (T-sites).